A Diversity Account of Bryaceae (Bryophyta: Musci) of Nepal - Pradhan, Nirmala; Joshi, Sanu Devi (Journal of Natural History Museum, 2009)
Bryums are diverse mosses distributed widely throughout the country. The species diversity of Bryaceae which were documented in various periods has been presented here. This paper includes 82 species including three subspecies and five varieties under seven genera of the total recorded 1150 bryofloral species in Nepal so far. Besides published records, the field survey of the first author within last five years has also been included here. Key words: Bryoflora; cosmopolitan; diversity; distribution; species Journal of Natural History Museum Vol. 23, 2008 Page 19-26